(untitled) - Akkerhuys, Zahra (London, 2009)
A White Paper that deals with the challenges presented by the global recession, climate change, and fragile and failing states. It reaffirms the Government's commitment to achieving the Millennium
Keywords: Poverty,Đói nghèo; International cooperation,Hợp tác quốc tế